2005
DOI: 10.1534/genetics.105.044966
|View full text |Cite
|
Sign up to set email alerts
|

Brc1-Mediated DNA Repair and Damage Tolerance

Abstract: The structural maintenance of chromosome (SMC) proteins are key elements in controlling chromosome dynamics. In eukaryotic cells, three essential SMC complexes have been defined: cohesin, condensin, and the Smc5/6 complex. The latter is essential for DNA damage responses; in its absence both repair and checkpoint responses fail. In fission yeast, the UV-C and ionizing radiation (IR) sensitivity of a specific hypomorphic allele encoding the Smc6 subunit, rad18-74 (renamed smc6-74), is suppressed by mild overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 63 publications
8
106
0
Order By: Relevance
“…On the basis of putative interaction between budding yeast Mms22p and Rtt107p (Ho et al 2002;Chin et al 2006), we hypothesized that if mms22 1 is the ortholog of MMS22, then mms22 and brc1 should show genetic epistasis if the two proteins function exclusively together. We observed that brc1D mutants grow with wild-type kinetics, but are sensitive to the same spectrum of DNA-damaging agents as mms22D, albeit at higher doses, and are not hypersensitive to IR or UV (Verkade et al 1999;Sheedy et al 2005; our own observations). Cells disrupted for both mms22 and brc1 showed a moderate synergistic growth defect compared to mms22D alone ( Figure 7B), suggesting that the two proteins do not function exclusively together.…”
Section: Identification Of S Pombe Mms22supporting
confidence: 54%
See 3 more Smart Citations
“…On the basis of putative interaction between budding yeast Mms22p and Rtt107p (Ho et al 2002;Chin et al 2006), we hypothesized that if mms22 1 is the ortholog of MMS22, then mms22 and brc1 should show genetic epistasis if the two proteins function exclusively together. We observed that brc1D mutants grow with wild-type kinetics, but are sensitive to the same spectrum of DNA-damaging agents as mms22D, albeit at higher doses, and are not hypersensitive to IR or UV (Verkade et al 1999;Sheedy et al 2005; our own observations). Cells disrupted for both mms22 and brc1 showed a moderate synergistic growth defect compared to mms22D alone ( Figure 7B), suggesting that the two proteins do not function exclusively together.…”
Section: Identification Of S Pombe Mms22supporting
confidence: 54%
“…Brc1 is thought to function primarily in S-phase where it aids in the replication of damaged DNA (Verkade et al 1999;Sheedy et al 2005). Brc1 was initially identified as a high-copy suppressor of smc6-74 (Verkade et al 1999), which encodes a subunit of the essential ''structural maintenance of chromosomes'' Smc5/6 complex that functions in chromosome organization and DNA repair (Lehmann et al 1995;McDonald et al 2003;Harvey et al 2004;Pebernard et al 2004Pebernard et al , 2006.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, TORC2-Gad8 mutant cells are insensitive to IR. The resistance of TORC2-Gad8 mutant cells to transient exposure to replicative stress is in contrast to the sensitivity of HR mutants, such as rad52 and rad51, to such conditions (67). Moreover, following a transient CPT treatment, which markedly elevates the number of Rad52 foci, we detected no major defects in returning to basal Rad52 foci levels in ⌬tor1 or ⌬gad8 mutant cells (Fig.…”
Section: Discussionmentioning
confidence: 66%